Current views on the potential for development of a HIV vaccine. (4th March 2017) - Cohen, Kristen W.; Frahm, Nicole
ABSTRACT: Introduction: Despite many recent advances in the HIV prevention landscape, an effective vaccine remains the most promising tool to end the HIV-1 pandemic. Areas covered: This review summarizes past HIV vaccine efficacy trials and current vaccine strategies as well as new approaches about to move into first-in-human trials. Expert opinion: Despite many setbacks in early HIV vaccine efficacy trials, the success of RV144 has provided the glimmer of hope necessary to invigorate the vaccine field, and has led to the development of a large number of vaccine strategies aiming at inducing an array of different immune responses. The follow-up pox-protein trials, developed to replicate and enhance the polyfunctional antibody responses induced by the RV144 regimen, are already reaching efficacy trials, while a large body of work providing a more complete understanding of the development of broadly neutralizing antibodies is now being translated into immunogen design using several different strategies. T-cell based vaccines, fallen out of favor after Ad5-based trials showed increased infection rates in Ad5 seropositive vaccine recipients, are experiencing a comeback based in part on the promising results from non-human primate challenge studies using rhCMV-based immunogens. This diverse array of vaccine candidates may finally allow us to identify a broadly effective HIV vaccine able to contain the epidemic.